2001
DOI: 10.1002/1521-396x(200101)183:1<41::aid-pssa41>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Radiative and Nonradiative Recombination Processes in GaN-Based Semiconductors

Abstract: Time-resolved optical characterization is an indispensable tool to study the recombination mechanisms of excitons and/or carriers based on radiative, non-radiative, localization and many-body processes. In this paper, we review the instrumentation of various spectroscopic techniques for the assessment of In x Ga 1--x N-based semiconductors such as time-resolved photoluminescence (TRPL), time-resolved electroluminescence (TREL), transient grating (TG) method to probe photothermal processes, microscopic TRPL usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 26 publications
(26 reference statements)
1
32
0
Order By: Relevance
“…samples with 10 nm GaN spacer layer thicknesses. The η int values of un-coated InGaN was estimated as 6 % at room temperature by assuming η int ~100% at ~6 K. 36 We found that the η int values were increased by 6.8 times (41%) by Ag coating and by 3 times (18%) by Al coating. We expect this actual enhancement of the η int values to be a result of the enhancement of the spontaneous recombination rate of electron-hole pairs by SP coupling.…”
Section: Internal Quantum Efficiencies and Purcell Enhancement Factormentioning
confidence: 99%
“…samples with 10 nm GaN spacer layer thicknesses. The η int values of un-coated InGaN was estimated as 6 % at room temperature by assuming η int ~100% at ~6 K. 36 We found that the η int values were increased by 6.8 times (41%) by Ag coating and by 3 times (18%) by Al coating. We expect this actual enhancement of the η int values to be a result of the enhancement of the spontaneous recombination rate of electron-hole pairs by SP coupling.…”
Section: Internal Quantum Efficiencies and Purcell Enhancement Factormentioning
confidence: 99%
“…Thus, the critical temperature T c indicating the saturation point of the intensities is 15 K. The internal quantum efficiency of the two LED samples can be estimated by the assumption that there is no nonradiative recombination process at the critical temperature. The internal quantum efficiency Z int can be written as Z int (%) ¼ I(T)/I(T c ) Â 100, where I(T) is the PL intensity at the temperature T, and I(T c ) is the PL intensity at the critical temperature T c [9]. By using this equation, the Z int of the LED on the FSS is calculated as 11%, and the Z int of the LED on the VGSS is 23%.…”
Section: Methodsmentioning
confidence: 99%
“…The latter parameter can be obtained from the ratio of the measured PL signals at room temperature and near 10 K. 16 An Arrhenius plot of the integrated output intensity of a sample from wafer A is shown in the inset of Fig. 3͑a͒, yielding a value of int of about 6.2%.…”
mentioning
confidence: 99%